Submissions of Correctional Inmates on the Trend and Patterns of Youth Involvement in Internet Fraud Activities in Ogun State, Nigeria - Folorunsho Muyideen OGUNMEFUN; Damilola AKINPELU; Oyeyemi Tolulope ALUKO; Ruth Ooreofe OGUNNOWO (PT Keberlanjutan Strategis Indonesia, 2025)
The growing trend of internet fraud globally among the youths and designed patterns for carrying out the menace is worrisome causing negating consequences of human and societal development.Th introduction of internet connote positive improvement and enhance human development but large number of Nigerian youths adopted the internet for fraudulent activities which dent the image of the country nationally and internationallyExtant literature were reviewed to justify the essence of the study while differential association and routine activity were adopted . Mixed methods and descriptive research design were adopted. The study was conducted in four correctional facilities in Ogun state (Ibara, Ilaro, Oba and Sagamu) where apprehended inmates of two hundred and eight-four were interviewed with the use of structured questionnaire while 10 in-depth interviews were conducted among 10 inmates using unstructured questionnaire.The concluded that various pattern such as identity thefts, dating scam, credit cards and fake bank cheque leave are the major scamming technique deployed to carry out there fraudulent activities. The study recommends that state law must be planned toward detaching youths in menace activity rather than encouraging the menace. The mindset of the apprehended fraudsters should be retrained to conform to the standard of social expectation of the society.